Enhancing urban resilience evaluation systems through automated rational and consistent decision-making simulations. (March 2022) - Rezvani, Seyed MHS; de Almeida, Nuno Marques; Falcão, Maria João; Duarte, Marta
Highlights: Urban resilience evaluation system (URES) is 16 indicators and 75 parameters. URES has five interrelated dimensions that used as scenarios in ARCDM. ARCDM is to pre-conceptualize and simulates scenarios for decision-makers. Virtual PoE (ARCDM) reduce time and resources on urban resilience decision-making. Abstract: Urban resilience is an increasingly important topic because of the need to protect and optimize the value derived from the urban built environment with its constructed assets. But there is still no harmonized definition or a consensual set of descriptors for this multi-dimensional concept. This paper aims to address this knowledge gap by outlining an Urban Resilience Evaluation System (URES) with a breakdown structure of 16 indicators and 75 parameters grouped into five interrelated dimensions: environmental, economic, organizational, social, and technical. The resilience scoring of the constructed assets relies on a novel Multi-Criteria Decision Analysis (MCDA) approach adapted from the Analytic Hierarchy Process (AHP) method. This novel approach involves Automated Rational and Consistent Decision Making (ARCDM) to pre-conceptualize and simulate behavior scenarios of a virtual panel of experts with different perspectives. These behavior scenarios are organized into a pairwise multilayer decision-making matrix that overrides the need for surveys. The authors use a portfolio of buildings with seven different use types (residential, research facilities, schools, hospitals, industrial facilities, shopping centers, and hotels) to test the applicability of the proposed URES breakdown structure for buildings with different levels of importance. This allows the comparison and validation of various ranges of results expressing different perspectives. The proposed methodology can be readily used by various stakeholders of the Architecture, Engineering, Construction, and Operation (AECO) sectors involved in the lifecycle management decisions and activities of constructed assets. It impacts feasibility studies, design, construction, operation and maintenance, rehabilitation, and disposal of constructed assets that comprise the built environment for cities and societies.